Representation and identity: A study of the Brussels 228 chansonnier and patronage in Margaret of Austria's court - Lamarre, Catherine (University of Ottawa (Canada), 2005)
This study examines the sixteenth century chansonnier, Brussels 228, which was compiled for Margaret of Austria (1480-1530). The analysis of the text, music, and gendered discourse found within will reveal how Margaret's status as a widow and a ruler influenced her musical patronage and the construction of this manuscript. In particular, the chansons Me fauldra il, Il me fait mal, and the two settings of Dulces exuvie will reveal the involvement of Margaret within the artistic production of her court. As well, an analysis of texts set to music within this chansonnier as well as by Josquin des Prez will examine the nature of his relationship with members of Margaret's court. The analysis of these works supports the underlying premise of this thesis, that Margaret manipulated the image of herself as widow along with existing societal conventions to produce a document that is an ideal expression of Margaret's patronage and her self.
Keywords: Music.